Dynamics Of Organizational Communications In Sharing Fantasy Themes To Maintain The Solidarity And Existence Of Community Organizations - Lerman Sinaga (Eduvest - Journal of Universal Studies, 2021)
The purpose of this study is to explain the organizational communication aspect of a community organization, Forum Betawi Rempug (FBR), and to reveal the interaction patterns and dynamics of various fantasies of dramatically exchanged symbols. Organizational communication can be defined as the process of creating and exchanging messages in a network of interdependent relationships to cope with an uncertain or changing environment. This research approach uses a subjectivist in the interpretive category. This study uses a qualitative method by using a Symbolic Convergence approach which is subjectivist. The results show that the dynamics of sharing fantasy patterns on the theme of leadership and Betawi figures of FBR community organization depart from the rhetorical vision of the issue of the revival of Betawi in the past, the era before the formation of the State and long before the Dutch colonial era existed. Betawi is a culture that is noble and needs to be fought for. In the organization’s context, FBR is a forum for the struggle to unite the Betawi people by evoking Betawi cultural values and the struggle for the Betawi people’s lives. From the narrative analysis of the FBR community organization, the present storytellers are the leaders in the ranks of the FBR. The latter is considered the primary source of information for delivering the message of the existing dramatic stories. The meaning of leadership in a metaphorical context often gives rise to stories of Betawi’s character and leadership as village guards in the sense of an essential struggle that contains sincerity and loyalty to the area where they live.